Concentration and retention of T oxoplasma gondii oocysts by marine snails demonstrate a novel mechanism for transmission of terrestrial zoonotic pathogens in coastal ecosystems - Colin Krusor; Woutrina A. Smith; M. Tim Tinker; Mary Silver; Patricia A. Conrad; Karen Shapiro (Environmental Microbiology, 2015)
Summary The parasite T oxoplasma gondii is an environmentally persistent pathogen that can cause fatal disease in humans, terrestrial warm‐blooded animals and aquatic mammals. Although an association between T . gondii exposure and prey specialization on marine snails was identified in threatened C alifornia sea otters, the ability of kelp‐dwelling snails to transmit terrestrially derived pathogens has not been previously investigated. The objective of this study was to measure concentration and retention of T . gondii by marine snails in laboratory aquaria, and to test for natural T . gondii contamination in field‐collected snails. Following exposure to T . gondii ‐containing seawater, oocysts were detected by microscopy in snail faeces and tissues for 10 and 3 days respectively. Nested polymerase chain reaction was also applied as a method for confirming putative T . gondii oocysts detected in snail faeces and tissues by microscopy. T oxoplasma gondii was not detected in field‐collected snails. Results suggest that turban snails are competent transport hosts for T . gondii . By concentrating oocysts in faecal pellets, snails may facilitate entry of T . gondii into the nearshore marine food web. This novel mechanism also represents a general pathway by which marine transmission of terrestrially derived microorganisms can be mediated via pathogen concentration and retention by benthic invertebrates.